2011
DOI: 10.1007/s11468-011-9225-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Extraordinary Optical Transmission in a Double Heterostructure Plasmonic Bandgap Cavity

Abstract: In this paper, a novel plasmonic bandgap cavity inducing the enhancement of extraordinary optical transmission is presented. Numerical simulations have been performed to model a free-standing structure made of a one-dimensional periodic arrangement of gold strips. Two different values of the lattice constant have been properly chosen to realize a double heterostructure-like cavity to accomplish extraordinary optical transmission assisted by the formation of a plasmonic bandgap in the adjacent regions. Numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Table 1 Table 1: Resonant wavelengths corresponding to the excitation of the SPP modes over the air-metal interface of the array of gold stripes with p = 700 nm and corresponding parameters for the equivalent structures. reports the resonant wavelengths of the SPP modes of the first order for the cases already presented in Figure 5 and the equivalent parameters obtained by the application of (6) and (7). The application of these parameters to the equivalent structure allows the comparison of spectra with those already exposed in Figure 5.…”
Section: Equivalent Structurementioning
confidence: 94%
See 2 more Smart Citations
“…Table 1 Table 1: Resonant wavelengths corresponding to the excitation of the SPP modes over the air-metal interface of the array of gold stripes with p = 700 nm and corresponding parameters for the equivalent structures. reports the resonant wavelengths of the SPP modes of the first order for the cases already presented in Figure 5 and the equivalent parameters obtained by the application of (6) and (7). The application of these parameters to the equivalent structure allows the comparison of spectra with those already exposed in Figure 5.…”
Section: Equivalent Structurementioning
confidence: 94%
“…Nevertheless, it only has a physical meaning for values of λ close to that one assumed by λ − res, m (θ) for a particular θ value. Moreover, the formulations (6) and (7) do not include the metal thickness, since it does not alter considerably the SPP resonance over the grating when the thickness itself is much larger than the skin depth of metal, that is, as in the presented cases.…”
Section: Equivalent Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Studies on shaping the metallic nanoslits are on-going [29,30]. Some complex structures, such as double layered metallic nanoslit array have also been investigated [31,32] In our previous work [35], it is reported that light coming out of a metallic nanoslit array can generate a unique optical curtain effect, i.e., the formation of a spatially invariant field distribution in the output region. Based on the physical model in the wave-vector domain, it is known that the optical curtain effect is actually the superposition of two diffracting plane waves ( 1 ± orders).…”
mentioning
confidence: 99%
“…Studies on shaping the metallic nanoslits are on-going [29,30]. Some complex structures, such as double layered metallic nanoslit array have also been investigated [31,32] to further explore the EOT phenomenon. Inside the 3 laboratory, researchers have already introduced metallic nanoslits into the technique of nanolithography in both near field [33] and far field [34].…”
mentioning
confidence: 99%